Cancer Literacy in Women: A Kap Exploration of Breast and Gynecological Cancers Accompanied by Cross-Sectional Based Online Survey in Tirupathi District - Nanda Kumar, Kopparapu Venkata; Gari Bindhu, Devarajappa; Likhitha, Kasireddy; Charani, Mekala Siva; Deepthi Priya, Nemali; Gowthami, Yaraganti (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Cancer is an illness caused by uncontrolled growth of cancer cells. Breast, cervical, ovarian, uterine cancers are among the most prevalent types of cancers in women. According to the 2020 report from the National Cancer Registry Programme (NCRP) under the Indian Council of Medical Research (ICMR), the risk of breast and other gynaecological cancers affects 1in 6 women. Acquiring knowledge about these cancers and adopting preventive measures or early detection methods can potentially save lives by treating them at an early stage when they are still localized and more manageable. Objective: To investigate the knowledge, attitude and practices concerning Breast and Gynaecological Cancers among women in Tirupati. Methods: A cross-sectional study is carried out among 600 women in Tirupati through an online survey. The study is aimed to gather information on their knowledge, attitude and practices regarding breast and gynaecological cancers. A pre-validated questionnaire was utilized to collect the necessary data. Results: In this study, a group of 600 women was included, spanning from 15 to 45 years of age. The majority of these participants demonstrated proficient knowledge, held a strong positive attitude, and regrettably, exhibited deplorable practice. Notably, out of these women, 104 had receive the HPV vaccine for the prevention of cancer. Conclusion: To improve women’s awareness and understanding, it is essential to introduce health education initiatives that aim to enhance their knowledge levels. The survey results indicate that the women surveyed demonstrated sufficient understanding and involvement in relation to breast and gynaecological cancers.